Optimalisasi Strategi Sertifikasi Halal Dalam Mendukung Islamic City Branding: Studi Eksplorasi pada Halal Center UIN Madura - Syafiqoh, Anilna; Fahrurrozi , Fahrurrozi; Muhtadi, Ridan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
Halal certification is important for the community in Pamekasan district to support and strengthen Islamic city branding. In achieving an Islamic city image, the UIN Madura halal center contributes by providing halal certification assistance. However, challenges such as competition, unmotivated business actors, complex requirements and processes, cost barriers, and policy changes hinder its implementation. Using a descriptive qualitative method, this study aims to identify and analyze the strengths, weaknesses, opportunities, and threats through a SWOT approach and IFAS-EFAS strategic factors in optimizing the halal certification strategy carried out by the UIN Madura halal center while supporting the Islamic city branding of Pamekasan district. Data collection techniques include interviews, observations, and documentation with the head of the UIN Madura Halal Center. The results of the study identified internal and external factors of the UIN Madura Halal Center, including halal assistants in each sub-district, a lack of halal assistants, a large Muslim population, and the threat of competition. The study also identified optimalization strategies for SO, WO, ST, and WT that can be used as steps to optimize the halal certification strategy.